2022
DOI: 10.1039/d1qi01288f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the luminescence of transition metal complexes with acyclic diaminocarbene ligands

Abstract: Organometallics featuring acyclic diaminocarbene (ADC) ligands have recently emerged as powerful emitters for use in OLEDs and other electroluminescent technologies. Owing to strong σ-donor properties and broad synthetic availability, ADCs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 169 publications
(348 reference statements)
0
33
0
Order By: Relevance
“…Moreover, ADCs are known to be even stronger σ-donors than NHCs due to the larger N–C carbene –N angles, which decrease the 2s character while increasing the 2p character in the σ orbital. Our group’s earliest efforts using ADCs to support luminescent metal complexes are represented by a series of bis-cyclometalated iridium complexes with chelated or cyclometalated ADC ancillary ligands, which include compounds that have efficient deep-blue phosphorescence . Similar structures have been investigated by Luzyanin’s group, and ADCs have also been used as supporting ligands for cyclometalated platinum complexes . Recently, our group has demonstrated the beneficial effects of ADC ligands in blue-phosphorescent platinum acetylide complexes, describing two cis -[Pt­(CNR)­(ADC)­(CCPh) 2 ] complexes ( 2a–2b ) derived from cis -[Pt­(CNR) 2 (CCPh) 2 ] precursors ( 1a–1b ), as shown in Scheme .…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, ADCs are known to be even stronger σ-donors than NHCs due to the larger N–C carbene –N angles, which decrease the 2s character while increasing the 2p character in the σ orbital. Our group’s earliest efforts using ADCs to support luminescent metal complexes are represented by a series of bis-cyclometalated iridium complexes with chelated or cyclometalated ADC ancillary ligands, which include compounds that have efficient deep-blue phosphorescence . Similar structures have been investigated by Luzyanin’s group, and ADCs have also been used as supporting ligands for cyclometalated platinum complexes . Recently, our group has demonstrated the beneficial effects of ADC ligands in blue-phosphorescent platinum acetylide complexes, describing two cis -[Pt­(CNR)­(ADC)­(CCPh) 2 ] complexes ( 2a–2b ) derived from cis -[Pt­(CNR) 2 (CCPh) 2 ] precursors ( 1a–1b ), as shown in Scheme .…”
Section: Introductionmentioning
confidence: 92%
“…Here we showed that azide addition to bis-cyclometalated iridium bis-isocyanide compounds gives access to a diverse set of new structures, with the fate of the reaction controlled primarily by the substituent pattern on the isocyanide with a secondary effect of the cyclometalating ligand. Previous work using isocyanide functionalization as a synthetic strategy for cyclometalated iridium complexes exclusively involved nucleophilic addition of nitrogen-based reagents, which gives access to acyclic diaminocarbenes. ,, The reactions described here lead to more diverse outcomes, and presumably all initiate with a [3 + 2] azide-isocyanide cycloaddition. This cycloaddition can give a stable tetrazolato when the isocyanide is substituted with electron-donating groups, which is followed by N 2 extrusion to leave an aryl cyanamido with electron-withdrawing groups.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging strategy in the design of cyclometalated iridium complexes and other classes of organometallic phosphors is to use ligand-based functionalization strategies to install supporting ligands not able to be accessed by traditional means. The best-developed example of this approach involves addition of a nitrogen-based nucleophile to a coordinated isocyanide, which forms an acyclic diaminocarbene (ADC). , Our group has used this method to install ADCs onto luminescent iridium , or platinum , complexes and showed the strong σ-donor ADCs are particularly effective at supporting efficient deep-blue phosphorescence, , and related approaches have been used to good effect by a few other groups in the design of iridium, , rhenium, or platinum , phosphors supported by ADCs.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal-based luminescent materials are a subject of rapidly growing interest in view of their applications for design and fabrication of solid-state lighting devices, in chemosensoring, and as photocatalysts. Efficient room temperature (RT) phosphorescence of transition-metal species is conventionally attributed to the heavy atom effect that induces strong spin–orbit coupling, which facilitates both fast intersystem crossing and the formally spin-forbidden triplet radiative decay. The photophysical and photochemical properties of transition-metal species, particularly those of platinum­(II), have been analyzed in a number of reviews. ,, …”
Section: Introductionmentioning
confidence: 99%